Mapping Undergraduate EFL Students’ Writing Anxiety: Trajectories from Responses, Reasons, and Strategies - Nugraheni, Dyah Ayu (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
Concerning the various responses of students’ anxiety on writing throughout the years, this sequential explanatory study aims to deeply explore the students’ writing anxiety and their reasons and strategies how to deal with it. The adapted questionnaire of Second Language Writing Anxiety Inventory and semi-structured interview were applied to examine students’ writing anxiety. Twenty five fourth semester students were sampled purposively, then they volunteered in the questionnaire and five of them were invited in the interview. The investigations revealed that among all types of anxiety, the students experienced most cognitive anxiety. The reasons for anxiety are linguistic difficulties, inadequate writing technique and practice, being afraid of tests, time pressure, and negative evaluation. The students’ strategies used for dealing with anxiety involve cognitive and affective aspects. These results can be a map in aiding students to cope with anxiety and suggests the important practical implications for teachers/lecturers and learners. Further, this study also discusses limitations and recommendations.